Wideband circularly polarized inverted cup shaped Hybrid Dielectric-Resonator Antenna over an Asymmetric Jerusalem cross-based metasurface - Zakaria, Zahriladha; Al Gburi, Ahmed Jamal Abdullah; Nalanagula, Rajasekhar; Kumari, Runa; Mohammed, Dunya Zeki; Darimireddy, Naresh Kumar (Electromagnetics Academy, 2025)
This article introduces a Circularly-Polarized (CP) inverted cup-shaped Hybrid Cylindrical-Dielectric-Resonator-Antenna (HCDRA) combined with an asymmetric Jerusalem cross unit-cell based metasurface (MTS). The antenna, designed for use in the 5G n-79 NR band (4400–5000 MHz) and IEEE 802.11n-WLAN (5 GHz) applications, features a unique disturbed coax-feed mechanism at the edge of cylindrical DR and an asymmetric MTS that boosts the circular polarization within the DR antenna. The antenna’s E-field and parametric analysis provide evidence of CP radiation. The proposed HCDRA achieves impressive S11 and Axial-Ratio (AR) bandwidths of 2.1 GHz and 740 MHz, with a maximum gain of 6.825 dBic. The overall gain obtained is consistently more than 5.5 dBic across the entire bandwidth of the HCDRA. The fabricated HCDRA is tested in an anechoic chamber, and the obtained practical results closely matched the simulation outcomes, confirming the performance of the proposed design.